Economic Vulnerability and Operational Efficiency in Indonesia’s Islamic Banking: A Vector Error-Correction Approach - Mubarok, Faizul; Wibowo, Martino; Pradana, Hasta Dwi; Ahmad, Rosimah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Amid Indonesia’s fast-growing Sharia-compliant finance sector and heightened global volatility, a clear assessment of how systemic shocks affect bank performance is increasingly urgent. This research analyzes economic vulnerability and its implications for the efficiency of Islamic banking in Indonesia. Using monthly time-series data from 2007 to 2024, it employs a Vector Error Correction Model (VECM). The findings reveal that both disbursed financing (FIN) and non-performing financing (NPF) significantly influence operational efficiency—measured by the BOPO ratio—in both the short and long run. Specifically, higher levels of FIN and NPF diminish efficiency by raising operational costs or reducing income. By contrast, the crisis indicator (CRS) gains significance only in the long run, implying that Islamic banks require time to adjust to macroeconomic shocks. Impulse-Response Function analysis shows mixed efficiency reactions to macroeconomic shocks, while Forecast Error Variance Decomposition highlights BOPO’s own shocks as the largest source of its variance and underscores NPF as the most powerful exogenous driver. These insights equip Islamic-bank managers and policymakers to craft strategies that mitigate economic vulnerability and enhance operational performance.